A Critical Assessment of Bias in Survey Studies Using Location-Based Sampling to Recruit Patrons in Bars. (19th September 2015) - Morrison, Christopher; Lee, Juliet P.; Gruenewald, Paul J.; Marzell, Miesha
Abstract : Location-based sampling is a method to obtain samples of people within ecological contexts relevant to specific public health outcomes. Random selection increases generalizability; however, in some circumstances (such as surveying bar patrons), recruitment conditions increase risks of sample bias. We attempted to recruit representative samples of bars and patrons in six California cities, but low response rates precluded meaningful analysis. A systematic review of 24 similar studies revealed that none addressed the key shortcomings of our study. We recommend steps to improve studies that use location-based sampling: (i) purposively sample places of interest, (ii) use recruitment strategies appropriate to the environment, and (iii) provide full information on response rates at all levels of sampling.